Asset markets in the lab: A literature review - Andrea Morone; Simone Nuzzo (Kiel Institute for the World Economy (IfW), 2016)
This paper aims at providing an overview of several topics that have been addressed in the field of experimental asset markets. Rather than being exhaustive in any single topic, this review is meant to gather the several research strands, and to provide a powerful picture of the main advances on the use of experimental techniques for the study of financial markets.
Keywords: 330; Experimental Asset Markets